(untitled) (KULT_online, 2012)
The altogether twelve articles of the anthology Fiktionen von Wirklichkeit. Authentizität zwischen Materialität und Konstruktion (Fictions of Reality. Authenticity between Materiality and Construction) explore the sociocultural meaning of authenticity from the perspective of different humanities-related and socioscientific disciplines. A specific characteristic of the book is that it takes into consideration the material preconditions for the construction of authenticity, which is an important supplement to currently dominating constructivist research approaches. The only weakness worth mentioning consists of a lack of a more detailed discussion of the concept of materiality itself. Apart from this minor flaw, however, the volume is able to highlight the enduring importance of ’authenticity’ in a conclusive and instructive manner